The SAGE handbook of popular music - Bennett, Andy 1963-; Waksman, Steve (London SAGE Publications Limited, 2015)
"The SAGE Handbook of Popular Music provides a highly comprehensive and accessible summary of the key aspects of popular music studies. The text is divided into 9 sections: Theory and Method; The Business of Popular Music; Popular Music History; The Global and the Local; The Star System; Body and Identity; Media; Technology; and, Digital Economies. Each section has been chosen to reflect both established aspects of popular music studies as well as more recently emerging sub-fields. The handbook constitutes a timely and important contribution to popular music studies during a significant period of theoretical and empirical growth and innovation in the field. This is a benchmark work which will be essential reading for educators and students in popular music studies, musicology, cultural studies, media studies and cultural sociology."--Publisher's description.
Part I. Theory and Method / Andy Bennett. The Many Worlds of Popular Music: Ethnomusicological Approaches / Kevin Dawe ; Notes on Sociological Theory and Popular Music Studies / Motti Regev ; Waiting for the Great Leap Forwards: Mixing Pop, Politics and Cultural Studies / Gilbert B. Rodman ; (Re)generations of Popular Musicology / Serge Lacasse ; Archival Research and the Expansion of Popular Music History / Christine Feldman-Barrett -- Part II. The Business of Popular Music / Steve Waksman. Power, Production and the Pop Process / Reebee Garofalo ; Intermediaries and Intermediation Devon Powers ; Popular Musical Labor in North America / Matt Stahl ; Music in Advertising in the US: History and Issues / Timothy D. Taylor -- Part III. Popular Music History / Steve Waksman. Grinding Out Hits at the Song Factory / Keir Keightley ; Popular Music Genres: Aesthetics, Commerce and Identity / David Brackett ; Live Music History / Matt Brennan -- Part IV. The Global and the Local / Andy Bennett. African, African American, Middle Eastern and French Hip Hop / Tony Mitchell ; Liminal Being: Electronic Dance Music Cultures, Ritualization and the Case of Psytrance / Graham St John ; Everything Louder than Everyone Else: The Origins and Persistence of Heavy Metal Music and Its Global Cultural Impact / Andy R. Brown ; Punk Rock, Hardcore and Globalization / Ross Haenfler -- Part V. The Star System / Steve Waksman. Rock Stars as Icons / David R. Shumway ; Everybody's in Show Biz: Performing Star Identity in Popular Music / Philip Auslander ; Midnight Ramblers and Material Girls: Gender and Stardom in Rock and Pop / Jacqueline Warwick ; Dark Cosmos: Making Race, Shaping Stardom / C. Riley Snorton -- Part VI. Body and Identity / Andy Bennett. Blurred Lines, Gender and Popular Music / Sheila Whiteley ; Popular Music, Race and Identity / Jon Stratton ; Dancing the Popular: The Expressive Interface of Bodies, Sound and Motion / Sherril Dodds ; Shaping The Past of Popular Music: Memory, Forgetting and Documenting / Catherine Strong -- Part VII. Media / Andy Bennett. In Print and On Screen: The Changing Character of Popular Music Journalism / Simon Warner ; Sight and Sound in Concert? The Interrelationship Between Music and Television / Tim Wall and Paul Long ; Viewing With Your Ears, Listening With Your Eyes: Syncing Popular Music and Cinema / Scott Henderson ; Beyond Napster: Popular Music and the Normal Internet / Nick Prior -- Part VIII. Technology / Steve Waksman. Phonography and the Recording in Popular Music / Patrick Feaster ; Ghosts of Electricity: Amplification ; Ubiquitous Musics: Technology, Listening and Subjectivity / Anahid Kassabian -- Part IX. Digital Economies / Steve Waksman. Modes of Production: The Value of Modal Analysis for Popular Music Studies / Tim J. Anderson ; Music, Copies and Essences / Joanna Demers ; Authorship, Ownership and Musical Appropriation / Kembrew McLeod ; Music Cartels and the Dematerialization of Power / Aram Sinnreich.
Includes bibliographical references and index.
Keywords: Popular music -- History and criticism; Popular music -- Handbooks, manuals, etc; Music theory; Sound recording industry